Mature cystic teratoma of the uterosacral ligament successfully treated with laparoendoscopic single-site surgery - Yu-Jin Koo; Kyong-Shil Im; Hyun-Ju Jung; Yong-Soon Kwon (Elsevier, 2012)
Objective: Although the majority of teratomas are encountered in the ovary, extragonadal mature cystic teratoma is an unusual disease entity, and the most common site is the omentum. Case Report: The occurrence of this tumor on a uterosacral ligament is extremely rare with enigmatic etiology. To our knowledge, there have been only three cases reported to date that describe a mature cystic teratoma of the uterosacral ligament, and this is the first report of successful treatment of these rare tumors with laparoendoscopic single-site surgery (LESS). Conclusion: In the present study, we report a mature cystic teratoma of the uterosacral ligament successfully treated with LESS in a 34-year-old woman with a preoperative diagnosis of mature cystic teratoma of the left ovary.